The Legal Standing of Deepfake Digital Evidence in Criminal Proceedings: Challenges of Evidentiary Integrity in the AI Era - Adrian Bima Putra (SEAN Institute, 2026)
The rapid advancement of Artificial Intelligence (AI) has introduced deepfake technology, triggering a crisis of authenticity regarding criminal evidence. This study aims to analyze the legal standing of deepfakes within the Indonesian criminal justice system and the challenges of maintaining evidentiary integrity during trials. Employing a normative legal research method, this study examines the synchronization between technological developments and current positive law regulations. The results indicate that while the ITE Law recognizes electronic information and documents as valid legal evidence, the emergence of deepfakes poses an existential threat to the